Distribution and Composition of Lobster Species Caught in Java Sea of East Java, Indonesia - Arief Setyanto; Nabilla Artini Rachman; Eko Sulkhani Yulianto (Universitas Gadjah Mada, 2018)
Lobster resources are abundant in Indonesia waters. Lobster’s catch production is known as an important fishery commodity. A lobster fishery is considered important fisheries within the Indonesia fishe ies management zone. So that, its management plan is needed to be developed. As a consequence, preliminary study on lobster distribution by its species proportion or composition in their catches by its fishing ground and fishing season (month) are important to mitigate the resources. The study was conducted in Java Sea of East Java to explore the lobster species distribution and composition. The Java Sea is laid within the Fisheries Management Zone of the Republic of Indonesia number 712. Lobster catch data were collected from 4 regions (landing bases) across East Java. They are Lamongan, Bawean, Tuban and Sumenep. The data was collected from December 2016 - March 2017. These regions are representing over all biogeography of marine ecology of East Java. Statistical test for homogeneity of composition/proportion of species of lobster by its regions or location and time/month were analyzed and tested statistically using one way Analysis of Variance (ANOVA). The results shows that the composition o lobster species in each regions or location in different time/month are different. There were our species o lobster identified. They are Panulirus ornatus, P. homarus, P. polyphagus, and P. Versicolor. P. ornatus found in those four locations. All 4 species are caught in Lamongan. there are no species of P. Homarus have been caught in Bawean. In Tuban there is 3 species of Panulirus ornatus, P. polyphagus, and P. homarus. While in Sumenep there are only two species which are P. ornatus and P. Versicolor. Panulirus polyphagus is dominant in Lamongan, Bawean, and Sumenep while P. homarus is in Tuban. Those four species were caught in the month of December, January, February and March with P. Polyphagus as a dominant catch.